Anorexia nervosa, advance directives, and the law: A British perspective. (29th April 2019) - Ip, Eric C.
Abstract: This article will explore whether the law should allow people with anorexia nervosa to refuse nutrition and hydration with special reference to the English decision in Re E (Medical Treatment: Anorexia) . It argues that the judge in that case made the correct decision in holding that the patient, who suffered from severe anorexia nervosa, lacked capacity to make valid advance directives under the Mental Capacity Act 2005 of the United Kingdom, and that medical procedures that are apparently against her wishes should be carried out for the sake of preserving her life. The law should generally not permit patients with anorexia nervosa to decline nutrition and hydration, precisely because their autonomous ability to make such decisions has been substantially circumscribed by this psychiatric condition.